Saudi-Iran rivalry in the Middle East: implication to national security - Mohammed, Ahmed Anwer; Ravichandran Moorthy, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The rivalry between Saudi Arabia and Iran has affected the regional security of the Middle East. Since 1979, Saudi-Iranian relations have been tensed due to the rivalry to gain relative power in the Middle East. Saudi-Iranian tensions are at their worst level in decades; not only there is a halt in diplomatic relations, the two countries are also involved in several proxy wars in Yemen, Syria and Iraq, besides the entanglements in the Sunni-Shia sectarian conflict. With these dynamics at play, the study aims to investigate how the Saudi-Iranian rivalry for power has impacted the regional security of the Middle East. Therefore, the study objectives: (i) to examine how Saudi-Iranian rivalry has created crisis in the Middle East, it argues that Saudi-Iranian rivalry has threatened national security in the Middle East. (ii) to investigate the role of external powers, such as the US, in the regional power balance of the Middle East. The study adopted a qualitative research method to arrive at the following findings: (i) the Iran-Saudi rivalry was found as a persistent feature in the politics of the Middle East, and (ii) this rival has destabilized the security and peace of the Middle East. This study provides in-depth insights into Middle East security and the survival strategies of these states.